Phenotypic and Genotypic Characteristics of Methicillin-Resistant Staphylococcus aureus Isolated from Dairy and Meat Products in Iran - M.M. Soltan Dallal; Z. Salehipour; M.K. Sharifi Yazdi; R. Bakhtiari; M. Abdi (Journal of Food Quality and Hazards Control, 2020)
Background: Methicillin-Resistant Staphylococcus aureus (MRSA) plays an important role in gastrointestinal diseases. The goal of this research was to determine phenotypic and genotypic characteristics of MRSA isolated from dairy and meat products in Iran. Methods: Ninety-three S. aureus isolates were prepared which had been obtained in our previous study. Antimicrobial susceptibility testing was done using disk diffusion method. The isolates were further analyzed by mecA gene detection. Staphylococcal Enterotoxins (SEs) and Toxic Shock Syndrome Toxin 1 (TSST1) were screened. Biotyping and molecular typing were done by short sequence repeats of spa and coa genes. Results: Five out of 93 S. aureus isolates (5.37%) included mecA. All five MRSA isolates were sensitive to at least six tested antibiotics and none were resistant to vancomycin. Furthermore, two isolates were multidrug resistant. Four isolates produced SEs and TSST1. Three out of 5 isolates were related to human biotype and two belonged to non-host-specific biotype. Conclusion: Presence of MRSA in dairy and meat products may be an important hygienic risk for the Iranian consumers, especially for immunocompromised people.